Fibrinogen Nijmegen : Congenital Dysfibrinogenemia Associated with Impaired t-PA Mediated Plasminogen Activation and Decreased Binding of t-PA - Engesser, Luzia; Koopman, Jaap; Munk, Gé de; Haverkate, Frits; Novéková, Irena; Verheijen, Jan H; Briët, Ernest; Brommer, Emile J P (Thrombosis and Haemostasis, 1988)
Congenital dysfibrinogenemia was found in a patient with venous thrombosis. Blood clot lysis was prolonged and suggested an impairment of fibrinolysis. We investigated whether this was related to the fibrinogen abormality. Fibrinopeptide release was normal but fibrin polymerization was defective in the patient. The stimulating effect of the patient’s fibrin on t-PA mediated plasminogen activation was impaired. This could not be attributed to defective binding of plasminogen. However, the binding of t-PA to the patient’s fibrin was about 16% less than to normal fibrin. A variant t-PA (G K1 K2 P), which contained only one of the two fibrin binding sites, i.e. the kringle-2 domain, was bound to the abnormal fibrin for only 50% of normal.We conclude that the prolongation of blood clot lysis and the impaired stimulation of t-PA mediated plasminogen activation are related to the defective binding of the kringle-2 domain of t-PA onto the fibrin moiety of the abnormal fibrinogen. The impairment of fibrinolysis might explain the occurrence of throm-bosis in the patient.
Keywords: Dysfibrinogenemia; Venous thrombosis; Impaired fibrinolysis; Fibrin binding of t-PA